Analisis Miskonsepsi Siswa SMA terhadap Konsep Hukum Newton Menggunakan Instrumen Four-Tier Diagnostic Test - Ahmad Fauzi Ramadhani; Nuri Handayani; Muhammad Rizky Pratama (Lembaga Publikasi Ilmiah Nusantara, 2026)
Misconceptions regarding Newton's Law concepts are among the most prevalent issues encountered in high school physics learning. This study aimed to identify and analyze misconceptions held by Grade XI Science students at SMA Negeri 1 Gunungsari toward Newton's Law concepts using a Four-Tier Diagnostic Test instrument. A descriptive quantitative research method was employed, involving 32 students as research subjects. The instrument consisted of 20 items of Four-Tier Diagnostic Test that had been validated by experts and tested for reliability. Results indicated that 38.7% of students experienced misconceptions regarding Newton's First Law (Inertia), 42.5% regarding Newton's Second Law (relationship between force and acceleration), and 35.2% regarding Newton's Third Law (action-reaction). The highest rate of misconceptions was found in the concept of friction force and the application of Newton's Second Law in everyday life. Students tended to believe that stationary objects have no forces acting on them and that action forces are always greater than reaction forces. These findings imply the need for more contextual and cognitive-conflict-based learning strategies to remediate existing misconceptions.